Aging process of population - Rosset, Edward (Pergamon Press, 1964)
Aging Process of Population investigates and analyzes the phenomenon of population aging. The text aims to provide a quantitative and qualitative analyses of structural transformations caused by the aging population on modern societies in various parts of the world. The book is organized into four parts. The first part deals with problems in methodologies, such as methods to measure demographic old age; hypothetical and perspective computation tools; and deficient methodological uniformity of source materials. The second part discusses the beginning of old age; analysis of life tables; and the.